The cocktail waitress - Cain, James M. (James Mallahan), 1892-1977 (Hard Case Crime book, 2012)
A rerelease of a classic tale by the New Yorker journalist and author of The Postman Always Rings. Following her husband's death in a suspicious car accident, beautiful young widow Joan Medford is forced to take a job serving drinks in a cocktail lounge to make ends meet and to have a chance of regaining custody of her young son. At the job she encounters two men who take an interest in her, a handsome young schemer who makes her blood race and a wealthy but unwell older man who rewards her for her attentions with a $50,000 tip and an unconventional offer of marriage.